THE ANALYSIS OF INFORMATION LITERACY SKILL THROUGH APLLICATION THE BIG 6 MODELS ON COLLEGE STUDENTS OF PGSD UNS KEBUMEN YEAR 2017 - Eko Andri Susilo; Istinganatuzzakiyah Istinganatuzzakiyah; Lhinatul Arivvia Rachma; Ratna Hidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This research analyzes the information literacy skills of undergraduate students class PGSD UNS Kebumen in daily lectures activities. Information literacy is ability to find, evaluate and use the information effectively. This research was conducted in September 2018. This research use a quantitative approach, which using questionnaire for data collection. The questionnaire was made based on The Big 6 Information Literacy Models. The conclusion of this research is that students calss of PGSD UNS Kebumen already doing six steps of The Big 6 : they dicuss with other in doing works, they prefer use search engine in finding information rather than searching in library, they doing simple searching strategies in finding information and they understand in using citation.